From Acenaphthenes to (+)‐Delavatine A: Visible‐Light‐Induced Ring Closure of Methyl (α‐Naphthyl) Acrylates. Issue 67 (30th October 2018) - Peez, Theodor; Luy, Jan‐Niclas; Harms, Klaus; Tonner, Ralf; Koert, Ulrich
Abstract: Disclosed herein is a visible light mediated cyclization of methyl (α‐naphthyl) acrylates and heteroaromatic analogues yielding substituted acenaphthenes and azaacenaphthenes. This highly functional‐group‐tolerant transformation was put to the test in an enantioselective formal synthesis of delavatine A. Mechanistic details were elucidated by DFT‐calculations revealing an unusual intramolecular H‐transfer mediated by a primary amine. The generality of this transformation enables a novel synthetic strategy of five membered ring annulation at an advanced stage, allowing reliance upon naphthalene chemistry up to the point of acenaphthene construction. Abstract : Hampered by harsh reaction conditions, the synthesis of functionalized acenaphthenes remains the key challenge in the exploration of their chemistry. Addressing this challenge, a visible light and amine‐catalyzed photocyclization is reported. Elucidation of the mechanism using DFT‐calculations and application in a formal synthesis of (+)‐delavatine A pave the way for further application.